Cultivating consciousness: an East-West journey - Rao, K. Ramakrishna (D. K. Printworld, 2014)
Papers presented at the conference on "Cultivating Consciousness for Enhancing Human Potential, Wellness and Healing", held at Durham during 8-10 November 1991